2018
DOI: 10.1002/acr.23494
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cane Use for the Management of Knee Osteoarthritis: A Cross‐Sectional Survey

Abstract: Independent determinants of cane use include older age, higher BMI, greater pain duration, and greater severity of knee pain. Strategies targeting an individual's capability and motivation to use a cane may increase cane use among people with knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…43 Our process measures (Appendix 5) also showed that participants were somewhat ambivalent about continuing to use the cane after the trial. Indeed, surveys have shown relatively limited uptake of canes by people with knee OA 29,44 and recruitment for our study progressed slowly, especially when compared to our other RCTs of non-drug and/or biomechanical interventions for knee OA. 45,46 Finally, approximately 1 in 5 cane users reported an adverse event which may have tempered symptom improvement or indirectly influenced adherence and/or the amount of force applied to the cane during the trial.…”
Section: Discussionmentioning
confidence: 99%
“…43 Our process measures (Appendix 5) also showed that participants were somewhat ambivalent about continuing to use the cane after the trial. Indeed, surveys have shown relatively limited uptake of canes by people with knee OA 29,44 and recruitment for our study progressed slowly, especially when compared to our other RCTs of non-drug and/or biomechanical interventions for knee OA. 45,46 Finally, approximately 1 in 5 cane users reported an adverse event which may have tempered symptom improvement or indirectly influenced adherence and/or the amount of force applied to the cane during the trial.…”
Section: Discussionmentioning
confidence: 99%